PEMIJATAN TITIK LI-4 DAPAT MENGURANGI NYERI KANULASI ARTERIOVENOUSFISTULA PADA PASIEN CKD YANG MENJALANI HEMODIALISA: STUDI KASUS - Anisa Uswatun Khasanah; Nurlaila Nurlaila (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Background, one of the vascular accesses used for hemodialysis is arteriovenous fistula. Arteriovenous fistula cannulation causes pain problems in patients. The cannulation procedure is felt as a painful sensation that needs to be treated, because the size of the needle used when cannulating an arteriovenous fistula is quite large compared to cannulating when installing an IV, namely 16 gauge. General purpose, to provide acute pain nursing care for Chronic Kidney Disease (CKD) patients undergoing hemodialysis in the hemodialysis room at RSU Aghisna Medika Kroya. Case collection method, pain scale measurement using a VAS instrument for 5 CKD patients undergoing hemodialysis without massage intervention and with massage intervention at the LI-4 point for 2 minutes or approximately 30-50 pressures. The results of nursing care, nursing care for acute pain in CKD patients undergoing hemodialysis after nursing for 1x4 hours with the application of massage at point LI-4 showed a decrease in the pain scale in patients without massage and with massage at point LI-4. In conclusion, LI-4 point massage therapy can be an therapeutic option to reduce the pain of arteriovenousfistula cannulation in CKD patients undergoing hemodialysis. Recommendation is hoped that more and larger case subjects will be taken in the next research so that the results will be more effective.